Migration inhibition of lymph node lymphocytes as an in vitro assay for cell-mediated immunity in the draining lymph nodes of parenterally immunized mice. - Mowat, A M (1982)
This paper describes a method for in vitro measurement of specific cell-mediated immunity in the mouse. Animals were immunized parenterally with ovalbumin in Freund's incomplete or complete adjuvant, and a direct migration inhibition assay was performed, using lymphoid cells from the draining lymph nodes. Migration inhibition was found to be antigen specific, correlated with systemic delayed-type hypersensitivity measured in vivo by skin testing, and had a high degree of sensitivity for ovalbumin. The migrating cells were identified as lymphocytes. Lymph node lymphocyte migration inhibition provides a reliable in vitro assay for regional CMI in the mouse.